Studi Komparasi Penggunaan Media Pembelajaran Whatsapp Group dan Google Classroom Terhadap Hasil Belajar IPA Kelas IX: Array - Nurul Qomariah (eductum: Jurnal Literasi Pendidikan, 2023)
This comparative study research aims to analyze the improvement of learning outcomes and analyze the effectiveness of the use of WhatsApp Group and Google Classroom Learning Media on learning outcomes. This quantitative approach is used to determine the increase in learning outcomes. The trial was carried out on 63 students at SMP N 1 Gabus, class IX F there were 32 students using WhatsApp Group and class IX G there were 31 students using Google Classroom. Data were collected by observation and documentation. The data on the effectiveness of learning media were analyzed with gain, normality, t-test at a significance level of 0.05. The results of the comparative study of class IX F at the first meeting the average acquisition is 83, the second meeting the average acquisition is 85, the third meeting the average acquisition is 87, the fourth meeting the average acquisition is 90. In class IX G meeting 1 the average acquisition 84.2 , meeting 2 an average of 85.5 , meeting 3 an average of 87.7 , meeting 4 an average of 90.5 . Based on the calculation of N-gain, obtained an increase in the results of the pre-test and post-test of class IX F of 0.67 in the medium category. Regarding the results of calculations in class IX G, there is an increase in N-gain with a score of 0.70 in the high category with an average pre-test score of 84 and post-test scores of 91. The significance value is 0.000 < = 0.05, which means there is a significant difference between the posttest mean so that H1 is accepted.